2017
DOI: 10.1103/physrevd.95.124035
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological solutions in generalized hybrid metric-Palatini gravity

Abstract: We construct exact solutions representing a Friedmann-Lema\^itre-Robsertson-Walker (FLRW) universe in a generalized hybrid metric-Palatini theory. By writing the gravitational action in a scalar-tensor representation, the new solutions are obtained by either making an ansatz on the scale factor or on the effective potential. Among other relevant results, we show that it is possible to obtain exponentially expanding solutions for flat universes even when the cosmology is not purely vacuum. We then derive the cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 70 publications
0
36
0
Order By: Relevance
“…(4. 14) In order that the solutions are stable we have to guarantee that the µ − of Eq. (4.14) is greater than µ c , i.e., 2a1(a2+a3+a4) 12a2a3−3a 2 4 > µ c .…”
Section: Stability Regimes: Sufficient Conditions On F (R R)mentioning
confidence: 99%
See 1 more Smart Citation
“…(4. 14) In order that the solutions are stable we have to guarantee that the µ − of Eq. (4.14) is greater than µ c , i.e., 2a1(a2+a3+a4) 12a2a3−3a 2 4 > µ c .…”
Section: Stability Regimes: Sufficient Conditions On F (R R)mentioning
confidence: 99%
“…The generalized hybrid metric-Palatini (GHMP) gravity arises as a natural outcome of the hybrid metric-Palatini gravity, where the action R + f (R) is replaced by a general function f (R, R) of both the Ricci and Palatini scalar curvatures [13]. This theory was studied in the context of cosmology, both with dynamical systems methods [13] and with reconstruction techniques [14], for which it was shown, among other behaviors, that exponentially expanding cosmological models exist even when the matter distribution is not purely vacuum. Also, asymptotically anti-de Sitter wormhole solutions with thin shells that satisfy the null energy condition for the whole spacetime were obtained in this theory [15].…”
Section: Introductionmentioning
confidence: 99%
“…Varying the action with respect to the field ϕ and to the field ψ yields after rearrangements, see [34],…”
Section: B Scalar-tensor Representation Of the Generalized Hybrid Mementioning
confidence: 99%
“…One can also find the scalar-tensor representation of this generalized hybrid metric-Palatini gravity, which now has two scalar fields. Exact solutions were constructed representing an FLRW (Friedmann-Lemaître-Robsertson-Walker) universe in a generalized hybrid metric-Palatini theory [34]. Among other relevant results, it was shown that it is possible to obtain exponentially expanding solutions for flat universes even when the cosmology is not purely vacuum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation